Prototype Pembangkit Listrik Tenaga Mikro Hidro - Puspita Ayu Armi; Sepdian (LPPM Politeknik Jambi, 2019)
Research on the design and construction of a micro hydro power plant has been conducted. This tool is used to support energy conversion learning, in this case a micro hydro power plant. In this research a series of steps were carried out including design, assembly, and testing. The plant uses a 12 VDC generator equipped with an inverter. From the test results it was found that this prototype has been able to produce electrical energy from a relatively small water flow, which starts from 1,9 m3/s by generating electricity of 0.03 watts. In this test the highest power measurement results obtained were 0.09 watts at the water discharge of 3,02 m3/s. Thus the greater water debit used, the bigger electricity produced will be.